An AIE‐Active Conjugated Polymer with High ROS‐Generation Ability and Biocompatibility for Efficient Photodynamic Therapy of Bacterial Infections. Issue 25 (11th March 2020) - Zhou, Taotao; Hu, Rong; Wang, Lirong; Qiu, Yanping; Zhang, Guiquan; Deng, Qiyun; Zhang, Haiyan; Yin, Pingan; Situ, Bo; Zhan, Chunlie; Qin, Anjun; Tang, Ben Zhong
Abstract: New, biocompatible materials with favorable antibacterial activity are highly desirable. In this work, we develop a unique conjugated polymer featuring aggregation‐induced emission (AIE) for reliable bacterial eradication. Thanks to the AIE and donor‐π‐acceptor structure, this polymer shows a high reactive oxygen species (ROS)‐generation ability compared to a low‐mass model compound and the common photosensitizer Chlorin E6. Moreover, the selective binding of pathogenic microorganisms over mammalian cells was found, demonstrating its biocompatibility. The effective growth inhibition of bacteria upon polymer treatment under light irradiation was validated in vitro and in vivo. Notably, the recovery from infection after treatment with our polymer is faster than that with cefalotin. Thus, this polymer holds great promise in fighting against bacteria‐related infections in practical applications. Abstract : Sunlight is the best disinfectant : A benzothiadiazole‐ and tetraphenylethene‐containing conjugated polymer (PTB‐APFB) with high ROS‐generation ability and selectivity for pathogenic microorganisms over mammalian cells was developed. In vitro and in vivo results show that PTB‐APFB inhibits growth of bacteria efficiently, leading to recovery from infection 3 days faster than cefalotin.